The necessity of digital transformation in commercial banks (Eurasian Journal of Humanities and Social Sciences, 2025)
This article provides information on the concept of the necessity of digital transformation in commercial banks and the current need for implementing the digital transformation process. It also provides an understanding of the main external factors of the emergence of systems for transforming banking system services, which play a significant role in the need to implement the digital transformation process, and highlights the need for the transition to digital transformation in commercial banks in Uzbekistan. In addition, conclusions and proposals are given on the development of the digital transformation process in commercial banks.